(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The Indian Legal System, largely being a colonial vintage, stresses on secrecy laws and such provisions are contained in Official Secrets Act 1923, sections 123,124 & 162 of the Indian Evidence Act 1872, the infamous Rowlatt Act 1919 and Bengal Criminal (Amendment) Act 1925 etc. After the birth of Republic, freedom of expression became a fundamental right under Art 19(1)(a) of the Constitution.